Atrial fibrillation in cryptogenic stroke and transient ischaemic attack – The Nordic Atrial Fibrillation and Stroke (NOR-FIB) Study: Rationale and design. (June 2019) - Ratajczak-Tretel, Barbara; Lambert, Anna Tancin; Johansen, Henriette; Halvorsen, Bente; Bjerkeli, Vigdis; Russell, David; Sandset, Else Charlotte; Ihle-Hansen, Hege; Eriksen, Erik; Næss, Halvor; Novotny, Vojtech; Khanevski, Andrej Netland; et al.
Purpose: Paroxysmal atrial fibrillation is often suspected as a probable cause of cryptogenic stroke. Continuous long-term ECG monitoring using insertable cardiac monitors is a clinically effective technique to screen for atrial fibrillation and superior to conventional follow-up in cryptogenic stroke. However, more studies are needed to identify factors which can help selecting patients with the highest possibility of detecting atrial fibrillation with prolonged rhythm monitoring. The clinical relevance of short-term atrial fibrillation, the need for medical intervention and the evaluation as to whether intervention results in improved clinical outcomes should be assessed. Method: The Nordic Atrial Fibrillation and Stroke Study is an international, multicentre, prospective, observational trial evaluating the occurrence of occult atrial fibrillation in cryptogenic stroke and transient ischaemic attack. Patients with cryptogenic stroke or transient ischaemic attack from the Nordic countries are included and will have the Reveal LINQ® Insertable cardiac monitor system implanted for 12 months for atrial fibrillation detection. Biomarkers which can be used as predictors for atrial fibrillation and may identify patients, who could derive the most clinical benefit from the detection of atrial fibrillation by prolonged monitoring, are being studied. Conclusion: The primary endpoint is atrial fibrillation burden within 12 months of continuous rhythm monitoring. Secondary endpoints are atrial fibrillation burden within six months, levels of biomarkers predicting atrial fibrillation, CHA2 DS2 -VASc score, incidence of recurrent stroke or transient ischaemic attack, use of anticoagulation and antiarrhythmic drugs, and quality of life measurements. The clinical follow-up period is 12 months. The study started in 2017 and the completion is expected at the end of 2020.